A human-derived neurovascular unit in vitro model to study the effects of cellular cross-talk and soluble factors on barrier integrity - Barberio, Chiara; Withers, Aimee; Mishra, Yash; Couraud, Pierre-Olivier; Romero, Ignacio A.; Weksler, Babette; Owens, Róisín M. (Frontiers in Cellular Neuroscience, 2022)
The blood-brain barrier (BBB) restricts paracellular and transcellular diffusion of compounds and is part of a dynamic multicellular structure known as the ‘neurovascular unit’ (NVU), which strictly regulates the brain homeostasis and microenvironment. Several neuropathological conditions, (e.g., Parkinson’s disease and Alzheimer’s disease) are associated with BBB impairment yet the exact underlying pathophysiological mechanisms remain unclear. 90% of drugs that pass animal testing fail human clinical trials, in part due to inter-species discrepancies. Thus, in vitro human-based models of the NVU are essential to better understand BBB mechanisms; connecting its dysfunction to neuro-pathological conditions for more effective and improved therapeutic treatments. Herein, we developed a biomimetic tri-culture NVU in vitro model consisting of 3 human-derived cell lines: human cerebral micro-vascular endothelial cells (hCMEC/D3), human 1321N1 (astrocyte) cells, and human SH-SY5Y neuroblastoma cells. The cells were grown in Transwell hanging inserts in a variety of configurations and the optimal setup was found to be the comprehensive tri-culture model, where endothelial cells express typical markers of the BBB and contribute to enhancing neural cell viability and neurite outgrowth. The tri-culture configuration was found to exhibit the highest transendothelial electrical resistance (TEER), suggesting that the cross-talk between astrocytes and neurons provides an important contribution to barrier integrity. Lastly, the model was validated upon exposure to several soluble factors (e.g., LPS, sodium butyrate and retinoic acid) known to affect BBB permeability and integrity. This in vitro biological model can be considered as a highly biomimetic recapitulation of the human NVU aiming to unravel brain pathophysiology mechanisms as well as improve testing and delivery of therapeutics.